Headmaster Management to Improve Teacher Performance in Singkawang Senior High Schools - Syahrudin Syahrudin (JETL (Journal of Education, Teaching and Learning), 2019)
The progress of education of a school as an educational institution is influenced by the role of the principal as an education manager. It is very much determined by the principal's ability to manage human resources from the planning to evaluation aspects. This study aims to reveal the management of school principals to improve the performance of teachers in Singkawang State High School 3 with a focus on 1) The description of the planning of quality improvement programs for teacher performance by the headmaster of State High School 3 Singkawang, 2) The implementation of programs to improve the quality of teacher performance by principals in State High Schools 3 Singkawang, 3) Program evaluation activities to improve the quality of teacher performance carried out by school principals in SMA 3 Singkawang. The research method used is descriptive research with a qualitative approach. Data collected by in-depth interviews, participant observation, documentation, and analyzed through data reduction, data presentation, conclusions or verification. Data reliability testing is done by extending the period of observation, and triangulation and member checking. The results of the study conclude 1) planning of quality improvement programs for teacher performance is carried out with reference to the vision and mission and school work plans. 2) implementation of improving the quality of teacher performance is carried out by holding a program of continuous professional development in the form of technical guidance (BIMTEK) learning development activities, In House Training (IHT) and workshops aimed at improving teacher competence and quality of learning, 3) Evaluation of teacher performance is carried out by carrying out activities academic supervision of teachers and managerial supervision of administration. Based on the results of the study suggested the following things: 1) planning for improving the quality of teacher performance, especially in school work plans need to be improved in a continuous professional improvement program. 2) The form of carrying out continuous professional improvement activities should be adjusted to what is required by the teacher. 3) Evaluation activities should be carried out consistently to improve teacher quality.